Dangerous waters : an adventure on Titanic - Mone, Gregory (New York : Roaring Brook Press, 2012)
Determined to focus on work rather than books, as his father had, twelve-year-old Patrick Waters leaves Belfast as a steward on the Titanic, but the very wealthy Harry Widener arranges to tutor him, drawing Patrick into association with thieves seeking Harry's very rare edition of Francis Bacon's Essays.
Keywords: Widener, Harry Elkins, -- 1885-1912 -- Juvenile fiction; Widener, Harry Elkins, -- 1885-1912 -- Fiction; Widener, Harry Elkins, -- 1885-1912.; Widener, Harry Elkins, -- 1885-1912 -- Fiction; Titanic (Steamship) -- Juvenile fiction; Titanic (Steamship) -- Fiction; Titanic (Steamship); Conduct of life -- Juvenile fiction; Books and reading -- Juvenile fiction; Brigands and robbers -- Juvenile fiction; Tutors and tutoring -- Juvenile fiction; Social classes -- Juvenile fiction; Conduct of life -- Fiction; Books and reading -- Fiction; Robbers and outlaws -- Fiction; Tutors and tutoring -- Fiction; Social classes -- Fiction; Books and reading; Brigands and robbers; Conduct of life; Social classes; Tutors and tutoring; Fiction. -- Conduct of life; Historical fiction; Fiction. -- Tutors and tutoring; Fiction. -- Books and reading; Fiction. -- Thieves; Fiction. -- Social classes; Historical fiction; Historical fiction; Fiction; Juvenile works; Historical fiction; Historical fiction